Constraining the KN coupled channel dynamics using femtoscopic correlations at the LHC - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Kroesen, Martin; Nath, Abhishek; Pachmayer, Yvonne C.; et al. (The European physical journal. C, Particles and fields, 2023)
The interaction of with protons is characterised by the presence of several coupled channels, systems like n and π with a similar mass and the same quantum numbers as the p state. The strengths of these couplings to the p system are of crucial importance for the understanding of the nature of the resonance and of the attractive p strong interaction. In this article, we present measurements of the p correlation functions in relative momentum space obtained in pp collisions at Te, in p–Pb collisions at Te, and (semi)peripheral Pb–Pb collisions at Te. ...
Im Titel erscheint das "K" der Zeichenfolge KN mit einem Querstrich
Gesehen am 09.11.2023
ALICE Collaboration: S. Acharya, V. Anguelov, A. Berdnikova, L. Bergmann, M.C. Danisch, V.J.G. Feuillard, P. Glässel, J. Kim, M. Kim, M. Kroesen, A. Nath, Y.C. Pachmayer, K. Reygers, R. Schicker, A. Schmah, G. Skorodumovs, J. Stachel, S. Stiefelmaier, M. Völkl, B. Windelband, A. Yuncu, F. Zanone [und 1024 weitere]